International legal cooperation in the field of criminal justice: new challenges and ways to overcome them - Ilchyshyn, N.; Brusakova, O. V.; Брусакова, О. В.; Krykun, V. V.; Крикун, В. В.; Myroshnychenko, Yu.; Оксана Брусакова (Journal of law and sustainable development. – 2023. – Vol. 11, № 4. – P. 1-14, 2023)
Сьогодні міжнародно-правове співробітництво у кримінальному судочинстві є однією з найважливіших складових правової системи кожної країни. Через зростання кількості міжнародних злочинів, таких як тероризм, кіберзлочинність, транскордонна злочинність та інші, які стали транснаціональними, потреба в ефективній міжнародній співпраці стає все більш важливою. У цій статті подано комплексний огляд принципів, форм та інструментів міжнародного співробітництва у кримінальних справах.

Purpose: Nowadays, international legal cooperation in criminal justice is one of the most important components of each country's legal system. Due to the growing number of international crimes, such as terrorism, cybercrime, cross-border crime and others that have become transnational, the need for effective international cooperation is becoming increasingly important. This article provides a comprehensive overview of the principles, forms and instruments of international cooperation in criminal matters. Method: The article uses general and special scientific methods. Results: The article emphasizes the importance of trust, mutual responsibility and cooperation, mutual legal assistance and protection of human rights as key principles of international cooperation. The article also considers various instruments of international cooperation, such as Interpol, Europol, the Hague Conference on Private International Law and others. Conclusions: The article argues that these instruments play a crucial role in facilitating crossborder cooperation and improving the effectiveness of criminal justice systems around the world. The article is a valuable contribution to understanding the importance of international cooperation in criminal justice and its impact on national legal systems. The article provides a clear explanation of the concepts and principles of international cooperation in criminal justice, its current problems, challenges, work currently underway to overcome them, and future plans to improve international cooperation in the field of criminal justice.

В настоящее время международно-правовое сотрудничество в области уголовного правосудия является одной из важнейших составляющих правовой системы каждой страны. В связи с ростом числа международных преступлений, таких как терроризм, киберпреступность, трансграничная преступность и других, которые приобрели транснациональный характер, необходимость эффективного международного сотрудничества становится все более важной. В данной статье дан комплексный обзор принципов, форм и инструментов международного сотрудничества по уголовным делам.

Propósito: Atualmente, a cooperação jurídica internacional em justiça criminal é um dos componentes mais importantes do sistema jurídico de cada país. Devido ao número crescente de crimes internacionais, como o terrorismo, a cibercriminalidade, a criminalidade transfronteiriça e outros que se tornaram transnacionais, a necessidade de uma cooperação internacional eficaz está a tornar-se cada vez mais importante. Este artigo fornece uma panorâmica abrangente dos princípios, formas e instrumentos da cooperação internacional em matéria penal. Método: O artigo utiliza métodos científicos gerais e especiais. Resultados: O artigo enfatiza a importância da confiança, responsabilidade e cooperação mútuas, assistência jurídica mútua e proteção dos direitos humanos como princípios-chave da cooperação internacional. O artigo também considera vários instrumentos de cooperação internacional, como a Interpol, a Europol, a Conferência da Haia de Direito Internacional Privado e outros. Conclusões: O artigo argumenta que estes instrumentos desempenham um papel crucial para facilitar a cooperação transfronteiriça e melhorar a eficácia dos sistemas de justiça penal em todo o mundo. O artigo é uma contribuição valiosa para a compreensão da importância da cooperação internacional na justiça penal e seu impacto nos sistemas jurídicos nacionais. O artigo fornece uma explicação clara dos conceitos e princípios da cooperação internacional na justiça penal, seus problemas atuais, desafios, trabalho em curso para superá-los e planos futuros para melhorar a cooperação internacional no campo da justiça criminal.
Cooperação jurídica internacional no domínio da justiça penal: novos desafios e formas de os superar
Keywords: publikatsii u WoS; criminal justice; international cooperation; international organizations; bilateral relations; Interpol; Europol; кримінальне правосуддя; міжнародне співробітництво; міжнародні організації; двосторонні відносини; Інтерпол; Європол; уголовное правосудие; международное сотрудничество